Surface tensions : searching for sacred connection in a media-saturated world - Roberts, Nathan (Peabody, Mass. : Hendrickson Publishers Marketing, LLC, 2016)
"A millennial through and through, Nathan Robert's book recounts his adventures in the new media jungle, blending personal experience with media theory, philosophy, literature, and theology to meditate on the question: How do we, and how should we, behave and believe in a media-saturated world? ... With humor and insight, Robert's story calls us to conceive of 'media' not only as a tangled postmodern phenomenon, a media jungle of befuddling proportions, but as a digital architecture that creates real meeting space where we can become ourselves, commune with others, and meet the God who created a world immediate, sensual, and oblique all at once, a world of surfaces illuminated by his presence"--Amazon.com.
Foreword / by Alissa Wilkinson -- Part One. From the self -- Spectacle -- Celebrity image -- Defiant comedy -- Part Two. Out of himself -- Film -- Voice -- Desire -- Conclusion: Sacred connection.
Keywords: Mass media -- Religious aspects -- Christianity; Social media -- Religious aspects -- Christianity; Mass media -- Social aspects -- United States; Roberts, Nathan; Generation Y -- United States -- Biography; Children of clergy -- United States -- Biography; Christian biography -- United States; Christianity and culture -- United States; Mass media and culture -- United States